Attitudes and emotions towards pain and sensitivity to painful stimuli among people routinely engaging in masochistic behaviour. (17th February 2015) - Defrin, R.; Arad, M.; Ben‐Sasson, M.P.; Ginzburg, K.
Abstract Background People engaged in masochistic behaviour (MB) seek to experience pain and the pleasure it evokes in sadomasochistic (S&M) sessions. The sensitivity and attitude to pain in these individuals has hardly been tested. We evaluated pain perception among these individuals and tested whether their experiences and attitudes towards pain are context‐related. Methods Thirty‐four healthy subjects participated; 17 routinely engaged in MB and 17 controls. Pressure pain threshold (PPT) was measured in two body regions. A structured questionnaire on S&M activities and context‐related pain experiences and emotions was completed, as well as the pain catastrophizing (CAT) and fear of pain (FOP) questionnaires. Results PPT was significantly higher among MB individuals and positively correlated with the frequency of S&M sessions. MB individuals also had lower levels of CAT, and FOP correlated negatively with the frequency of MB and the number of body regions involved. Pleasure evoked during S&M sessions correlated positively with pain intensity and number of body regions involved. Pain in everyday life correlated negatively with MB activities. However, the emotional attitude to everyday pain was ambivalent: MB individuals perceived pain intensity and unpleasantness similar to the controls, but simultaneously gained pleasure from the pain. Conclusions MB individuals exhibited pain hyposensitivity, presumably resulting from frequent engagement in MB. Alternatively, these subjects may have a predisposition which enables this engagement. Attitudes towards pain in MB individuals are complex. They appear to be context‐related with pain experienced as pleasurable and rewarding during S&M sessions, and negative but still pleasurable in everyday life.